Effective training strategies :a comprehensive guide to maximizing learning in organizations - Davis, James R. (Berrett-Koehler Pub. San FranciscoUS, 1998)
Argues that as learning assumes new significance in organizations, a broader definition of training needs to be developed. Looks at how organizations arrange for learning, and establish a philosophy of learning. Provides techniques for planning for learning. Examines 7 training strategies namely: the behavioral, cognitive, inquiry, mental models, group dynamics, virtual reality, and holistic strategies. Discusses purposes, types, and principles of the assessment of learning.